Dual‐Modal Fluorescence‐SERS Detection of Blood Glucose Engineered by Hierarchical Laser‐Induced Micro/Nano Structures for Diabetes Screening. Issue 19 (7th June 2022) - Lu, Libin; Guan, Shihe; Guan, Yingchun; Hong, Minghui
Abstract: Surface‐enhanced Raman spectroscopy (SERS) is a highly sensitive and selective vibrational spectroscopy, which has promising application in diabetes detection. However, the current detection methods usually suffer from poor reproducibility, time‐consumption, and complicated fabrication procedures, which limit their practical applications for large‐scale diabetes screening. Herein, a one‐step laser fabrication method to realize the integration of SERS and surface‐enhanced fluorescence (SEF) is introduced for rapid detection of glucose by generating controllable hierarchical laser‐induced periodic surface structures (LIPSS) on Si substrate. The proposed dual‐modal detection is to use SEF for first rapid qualitative analysis, and to apply SERS for later quantitative analysis of the glucose concentration. The SERS and SEF enhancement is up to 2.11 × 10 6 and 24.83, respectively, while the detection limit of SERS and SEF is × 10 −9 and 1 × 10 −6 mol L −1, respectively. Moreover, clinical verification of this dual‐modal detection of glucose in human blood samples is investigated, and the results are in good agreement with the clinical report. The present SERS‐SEF dual‐modal detection provides a facile and promising method for large‐scale diabetes screening. Abstract : A simple and highly sensitive dual‐modal surface‐enhanced Raman spectroscopy‐surface‐enhanced fluorescence platform is developed through one‐step femtosecond laser fabrication technique. After functionalizing with carbohydrate recognition molecules, the dual‐modal platform is used for human blood‐based diabetes diagnosis via surface‐enhanced Raman and fluorescence.